2022
DOI: 10.3390/biomedicines10030634
|View full text |Cite
|
Sign up to set email alerts
|

Increased Placental Anti-Oxidant Response in Asymptomatic and Symptomatic COVID-19 Third-Trimester Pregnancies

Abstract: Despite Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) -induced Oxidative Stress (OxS) being well documented in different organs, the molecular pathways underlying placental OxS in late-pregnancy women with SARS-COV-2 infection are poorly understood. Herein, we performed an observational study to determine whether placentae of women testing positive for SARS-CoV-2 during the third trimester of pregnancy showed redox-related alterations involving Catalase (CAT) and Superoxide Dismutase (SOD) antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
(72 reference statements)
0
2
1
Order By: Relevance
“…The representative marker of lipid peroxidation is TBARS [26]. Higher TBARS were reported in the plasma of women diagnosed with COVID-19 compared with controls [38]. These results are in contrast with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…The representative marker of lipid peroxidation is TBARS [26]. Higher TBARS were reported in the plasma of women diagnosed with COVID-19 compared with controls [38]. These results are in contrast with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…Levels of thiobarbituric acid (TBARS) (lipid peroxidation marker), hypoxia inducible factor 1 alpha (HIF-1a), catalase (CAT), superoxide dismutase (SOD), and glutathione synthetase (GSS) are higher in SARS-CoV-2 positive placentas, indicating perturbations in hypoxic response and mitochondrial physiology [ 30 , 34 ]. Respiratory chain subunit genes NADH:Ubiquinone oxidoreductase subunit A9 (NDUFA9), succinate dehydrogenase complex flavoprotein subunit A (SDHA) and cyctochrome C oxidase subunit 4I1 (COX4I1) were also decreased in symptomatic infected cases [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…investigated placental HIF-1α level in third-trimester pregnancies with asymptomatic and symptomatic COVID-19 patients. They found that overexpression of HIF-1α in the placenta of pregnant patients with asymptomatic and symptomatic COVID-19 [ 34 ]. In our study, HIF-1α showed an increased level of mRNA expression in all patients than healthy individuals.…”
Section: Resultsmentioning
confidence: 99%